Grid connected with micro solar generator - Shariff, Mohamad Findyrul (2015)
Nowadays, the need of renewable energy sources in on the rise because of the acute energy crisis in electricity generation due to increasing consumption demand and populations. Thus, energy from the sun is the best option for the generation of electricity as it is available everywhere, pollution-free as well as is free to harness. Therefore, objective of this dissertation is to generate simulation framework of the grid connected micro solar generator and analyse its efficiency and performance which can benefits to both educational institutions and industrial field. A framework system has been done to extract maximum obtainable solar power from the photovoltaic array and converted it into alternating current before deliver to the utility grid through controlling and synchronization mechanisms. The system includes photovoltaic array, maximum power point tracker (MPPT), DC-DC boost converter, three-phase inverter, modulation techniques, voltage source controller (VSC) controller and utility grid. Overall findings indicate the implementation of the developed framework can be useful for the further investigation and improvement of the grid connected photovoltaic (GCPV) system. In addition, result also indicate that framework system have a lower total harmonic distortion of 1.17%. The simulation studies are carried out in Simulink MATLAB environment.